1995
DOI: 10.1084/jem.182.6.1807
|View full text |Cite
|
Sign up to set email alerts
|

Complement-mediated regulation of tissue factor activity in endothelium.

Abstract: SummaryInflammation and immunity may be associated with endothelial cell (EC) injury and thrombus formation . We explored the mechanisms through which a humoral immune response directed against the endothelium might promote coagulation . Using the interaction ofanti-EC antibodies and complement (C) with cultured EC as a model, we studied the expression and function of tissue factor, a cofactor for factor VIIa-mediated conversion offactor X to Xa. Exposure of EC to anti-EC antibodies and C in sublytic amounts s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(164 citation statements)
references
References 52 publications
2
161
0
1
Order By: Relevance
“…Del Papa et a1 showed that AECA induced endothelial synthesis of IL-lp, leading to ELAM-1 expression (38). Saadi et a1 showed that complement-induced TF production by endothelial cells was mediated by IL-la (36). This role of IL-la is also supported by data from Carlsen et a1 (40), who showed that recombinant IL-la induced a concentrationdependent increase in endothelial cell TF activity, an effect that was stronger at 6 hours than at 16 hours.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Del Papa et a1 showed that AECA induced endothelial synthesis of IL-lp, leading to ELAM-1 expression (38). Saadi et a1 showed that complement-induced TF production by endothelial cells was mediated by IL-la (36). This role of IL-la is also supported by data from Carlsen et a1 (40), who showed that recombinant IL-la induced a concentrationdependent increase in endothelial cell TF activity, an effect that was stronger at 6 hours than at 16 hours.…”
Section: Discussionmentioning
confidence: 80%
“…This potentially indicated that the effect observed with anti-PR3-stimulated HUVEC involved intracellular pathways that require protein synthesis (Figures 2 and 3). To identify this intracellular pathway, we investigated whether IL-1 a mediated the response (36)(37)(38). We therefore looked for IL-la synthesis by measuring IL-la mRNA by RT-PCR in anti-PR3-stimulated HUVEC.…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Such events may create medullary vascular congestion and accumulation of intravascular leukocytes. Additionally, activation and injury of endothelial cells may induce a procoagulant response (34), leading to the formation of thrombus in the microvasculature. This congestion and thrombosis may in turn impair oxygen delivery to the outer medulla, resulting in an "extension phase" of ischemia which compounds the initial IR assault (17).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory Investigation • June 2000 • Volume 80 • Number 6 develop in discordant porcine xenografts as a consequence of complement activation, inflammation, and the secondary development of a procoagulant state Ierino et al, 1998;Lawson and Platt, 1996;Robson et al, 1996;Saadi et al, 1995). Alternatively, vascular thrombosis may be promoted by cross-species molecular incompatibilities between activated primate coagulant factors and donor anticoagulant proteins expressed on the graft vasculature .…”
Section: Mechanisms Of Acute Humoral Xenograft Rejectionmentioning
confidence: 99%